From Disabled to Differently Abled: Intersectionality and Universal Design as Foundations for Inclusive Classrooms in Higher Education - (:unkn) unknown (My University, 2025)
This dissertation explores the experiences that students with disabilities (SWDs) from diverse sociodemographic backgrounds encountered beginning with their transition from high school to higher education and how on-ramps to seeking disability accommodation posed challenges in the university and college setting. I used a qualitative methodology to analyze, interrogate, and develop a constructivist grounded theory to inform interuniversity policy on principles of Universal Design (UD), the Universal Design for Learning, and the Universal Design of Instruction (UDL and UDI) frameworks to benefit SWDs from a diverse sample enrolled in urban higher education institutions (HEIs) in the Midwest region of the United States. These retrospective accounts of their experience in high school aided in expanding the current body of literature on the role that ableism plays in affecting SWDs’ educational trajectories, specifically those with multiple marginalized identities. In other words, this dissertation uncovered the implicit and explicit biases that affected the well-being of differently abled students. By gathering a series of themes compiled from participants’ perspectives, current disability accommodation models in institutions of higher education were scrutinized from a different angle of inquiry not looking at issues solely incepted at the university itself but by identifying a potential myriad of long-term hardships faced by participants. The goal of this study was to provide deeper understanding for HEIs to provide better on-ramps for disabled students in terms of inclusivity, overall well-being, a sense of belongingness, easier navigation through the physical environment, and universally designed learning environments to increase retention and graduation rates for the student population since many disabled students choose not to document and self-disclose their disability. What are the accounts of SWDs (across race, gender, SES, and orientation) to inform university policy on the implementation of UD, UDL, and UDI?
Keywords: Disability studies; Education policy; Sociology; higher education; students with disabilities; universal design; universal design for learning; universal design of instruction; urban serving universities and colleges